Constantes de Movimento para um Potencial Dependente da Velocidade - Castro, A. S. de [UNESP]; Marchesetti, E. L. [UNESP]; Feldt, A. [UNESP] (Sociedade Brasileira de Física, 2002)
Simetrias geométricas contínuas para um sistema fechado de partículas são investigadas. Por suposto, as interações são deriváveis de uma função potencial dependente das velocidades das partículas. Tanto os vínculos sobre a forma da função potencial quanto os princípios de conservação resultantes das simetrias espaço-temporais contínuas são derivados. A lagrangiana de Darwin é utilizada como ilustração para o caso do movimento lento de cargas elétricas na formulação deMaxwell-Lorentz da eletrodinâmica clássica. O momento linear, o momento angular e a energia, quantidades dependentes de calibre, são obtidos.

Geometric continuous symmetries for a closed system of particles are investigated. It is supposed that the interactions are derivable from a velocity-dependent potential. Both the constraints on the form of the potential and the conservation principles resulting from the continuous space- time symmetries are derived. Darwin's Lagrangian is used as an illustration for the case of electric charges in slow motion in Maxwell-Lorentz's formulation of classical electrodynamics and the gauge-dependent linear momentum, angular momentum and energy are obtained.
Constants of motion for a velocity-dependent potential